Guia informativo para gestantes sobre sífilis congênita - Amorim, Nadyne Dayonara Maurício de (2020)
Brazil has experienced a scenario of high incidence of syphilis since 2010, leading to the announcement of the Ministry of Health about the epidemic of the disease in Brazil. The disease is curable, unique to humans and transmitted through sexual intercourse from the bacterium Treponema Pallidum. Syphilis acquired, syphilis in pregnant women and congenital syphilis are the possible types of the disease. Unlike the others, congenital syphilis is transmitted from mother to child during pregnancy or childbirth if the mother is not diagnosed or treated during the gestational period. This type of syphilis showed a 300 percent increase in registrations of new cases in the country. The information presented is alarming and presumes possible circumstances experienced in Brazil. Given that the incidence rate of congenital syphilis is increasing sharply, it is possible to state that the number of new syphilis cases in pregnant women, as well as the incidence of a gap in the diagnosis and treatment of the disease, also presents worrying numbers. During prenatal care, the mother undergoes syphilis testing every trimester and this test is repeated monthly if the pregnant woman is diagnosed with syphilis. Two tests are performed in the diagnosis of syphilis. The rapid test is used as the first test and results in a maximum of 30 minutes. If the result is reactive (there is an etiological agent present), the individual should perform the second test, the VDRL, which has its result presented in about seven days. Due to the severity of the scenario in which the baby may be subjected if the individual is a pregnant woman, treatment with benzathine penicillin should begin immediately, in other words, even before receiving the VDRL. It is curious to think that with the decrease in congenital syphilis cases, there is a decrease in syphilis cases for a future population. Proper prenatal follow-up, as well as proper follow-up of treatment instructions for the disease should be followed so that syphilis, which is millennial, becomes only in the history of Brazil.